SUICIDAL ISONIAZID POISONING - Khoharo, Haji Khan; Ansari, Shuaib; Abro, Allauddin; Qureshi, Fatima (Journal of Ayub Medical College Abbottabad, 2009)
Accidental or intentional Isoniazid poisoning may manifest within half to three hours as intractable seizure, acidosis, and coma. Single high dose of pyridoxine was used as an antidote with good response as reported earlier. Ingestion of more than 80 mg/kg body weight produces severe central nervous system symptoms and a dose of 125 mg/kg is potentially lethal if not promptly treated. We report a case of suicidal attempt with use of Isoniazid, who developed grand mal seizures and was controlled with diazepam and symptomatic treatment. Keywords: Isoniazid, INH, grand mal, suicidal attempt, poisoning